Development of Competency Test Modules for Culinary Skills in Food Processing and Serving Subjects in the Professional Education for Junior High School Teachers in the Catering Expertise Study Program - Nurfalakha, Tya (Universitas Negeri Semarang, 2020)
The teacher is an important component in the teaching and learning process. A teacher participates in efforts to form potential human resources in the field of development. Teachers who have received educator certificates mean that they are considered professionals in creating quality education systems and practices. The results of the teacher competency test that occurred by vocational school teachers got an average of 50.2 lower than high school teachers, this means that the skill competency test for each skill competency is less specific in certain subjects. The purpose of this study was to develop a learning module for processing and serving food in Teacher Professional Education (PPG). This research applies the development method or R and D. The design chosen is ADDIE, which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The unit of analysis in this research is the learning module for processing and serving food in Teacher Professional Education (PPG). The instruments used in this study were (1) an assessment sheet of the learning module on food processing and presentation of Teacher Professional Education (PPG); (2) a practical questionnaire for the learning module for processing and serving food in Teacher Professional Education (PPG); and (3) a questionnaire to measure the effectiveness of the learning module for the processing and presentation of food in Teacher Professional Education (PPG). The data analysis used in this study were (1) categorical to determine the feasibility level of the Food Processing and Serving Learning module in Teacher Professional Education (PPG); (2) the Guttman category to determine the practical level of the learning module in the processing and presentation of food in Teacher Professional Education (PPG) using the Kr and Ks coefficients; and (3) N-Gain and N-Gain difference test using the t-test, to determine the effectiveness of learning processing and serving of food in Teacher Professional Education (PPG). Based on the feasibility test, practicality test, and the effectiveness test of the learning module for the processing and presentation of food in the Teacher Professional Education (PPG) that was developed, according to the lecturers' responses as media experts, the responses of the culinary study program teachers obtained the response criteria for learning food processing and serving in professional education The teacher (PPG) is very feasible, the responses from teachers and students are as user responses, the practicality of the module obtains very practical assessment criteria, from the effectiveness test in the experimental class, the module obtains effective criteria.